The Impact of Audit Quality Factors on Investor Confidence in Vietnamese Capital Markets: The Moderating Role of Financial Literacy - Huong, Hoang Dinh; Huong, Pham Thanh; Tu, Tran Thi Ngoc (Indian Journal of Information Sources and Services, 2025)
This research examines the effects of audit quality characteristics and the moderating effect of financial literacy on the investor confidence in the capital market in Vietnam. This study fills the gap in the existing literature by analyzing perceptions of financially sophisticated investors on attributes of audit quality like Reputation of the Audit Firm, Timeliness of the Audit, Transparency of the Audit, and Compliance with the Rules and Standards of Auditing. The primary objective of the study is to determine whether investors, particularly those with financial literacy, lower their confidence due to perceived lack of control over finances and whose perceptions are shaped by financial literacy. Using quantitative techniques, data was gathered via questionnaires from 315 individual and institutional investors in the Vietnamese financial market which using three step hierarchical regression analysis (MRA) to explore the relationship between the variables. The findings indicated that audit quality attributes are critical to enhancing investor confidence, while the enhanced knowledge of finance mitigated the adverse influence of the Reputation of the Audit Firm, Transparency of the Audit, and Compliance with Rules and Standards of Auditing. The finding of this study, however, is that there was no significant moderation effect discovered on the timeliness of the audit. Based on the findings it can be concluded that although audit quality is fundamental to trust in the financial information of the company, it is clear that financially literate investors do not tend to repose much trust in the assurance of the results of the audit, but rather, on another financial analysis conducted their own analyses independently. For auditing firms and regulators in Vietnam, this statement highlights the need to bolster the credibility of audits while enhancing transparency and timeliness of reporting in order to retain investor trust. This research helps in understanding the relationships between the quality of audits and the actions of investors, giving useful insights for developing financial markets which have comparable circumstances as Vietnam.